Retinal toxicity after repeated intravitreal carboplatin injection into rabbit eyes - Pochop, Pavel; Darsova, Denisa; Uhlik, Jiri; Lestak, Jan; Kukacka, Jiri; Kodetova, Daniela; Klapkova, Eva; Malis, Josef; Vajner, Ludek (Biomedical papers, 2014)
Background: The aim of this study was to assess retinal toxicity in a rabbit model after carboplatin delivered as repeated transcorneal intravitreal injection, in order to determine the highest possible safe dose for use in human retinoblastoma "seeding" tumor chemotherapy.Methods and Results: We used six albino rabbits in an in vivo experiment and injected 0.008 mg of carboplatin intravitreally (iv) 4 times at two-week intervals. 0.08 mL saline was injected into the left eye. We recorded electroretinograms (ERGs) before the first carboplatin injection and after the fourth injection. Platinum concentration was measured 1 h after the fifth additional injection. We found reduced dark-adapted b-wave amplitudes and, light-adapted b-wave and a-wave amplitudes. The differences between right and left eyes was significant but we found no histopathologic retinal changes.Conclusions: 0.008 mg of carboplatin is probably the highest possible safe dose for the treatment of retinoblastoma patients. Questionable is direct extrapolation of retinal toxicity from the rabbit eye model to the human eye.
Keywords: carboplatin concentration; electroretinogram; intravitreal seeding; local treatment; rabbit; retinoblastoma